Participation at the periphery: community participation in reformed local government structures - O Broin, Deric (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
This paper briefly examines the current local government structures in Ireland and, in particular, the role and experience of the newly established structures in Fingal County Council and Dublin Corporation. The example of the existing community participation mechanisms on the Strategic Policy Committees and the City and County Development Boards of both local authorities will be examined. Finally, it puts forward proposals for community and citizen participation on the Local Area Committees.
Keywords: Urban geography -- Ireland